Penyuluhan Program Budidaya Petani Jamur Tiram Putih Millenial - Novyarni, Nelli; Kartijo; Harni, Reni (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
White oyster mushrooms have high nutritional value and provide health benefits. However, challenges in optimizing production, knowledge, and marketing strategies for white oyster mushrooms include yield fluctuations, high production costs, tight market competition, and a lack of teaching staff who are experts in white oyster mushroom cultivation. This research aims to counsel Villa Mushroom Agrifarm entrepreneurs regarding mushroom cultivation education, reducing production costs, and designing marketing strategies to increase sales volume. The extension method is carried out through an interactive approach, where Community Service Program (P2M) participants are given explanations, counseling, direct direction, and material about the white oyster mushroom cultivation program for millennial farmers.